2019
DOI: 10.1126/sciadv.aaw6703
|View full text |Cite
|
Sign up to set email alerts
|

Protein lysine de-2-hydroxyisobutyrylation by CobB in prokaryotes

Abstract: Lysine 2-hydroxyisobutyrylation (Khib) has recently been shown to be an evolutionarily conserved histone mark. Here, we report that CobB serves as a lysine de-2-hydroxyisobutyrylation enzyme that regulates glycolysis and cell growth in prokaryotes. We identified the specific binding of CobB to Khib using a novel self-assembled multivalent photocrosslinking peptide probe and demonstrated that CobB can catalyze lysine de-2-hydroxyisobutyrylation both in vivo and in vitro. R58 of CobB is a critical site for its d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 41 publications
0
80
0
Order By: Relevance
“…Some writers and erasers in bacteria are versatile in modifications of proteins with various acylations. For examples, CobB has been shown as a de-acetylase in E. coli and as a dehydroxybutyrylase in Proteus mirabilis 50 . Acetylation and succinylation are two representative PTMs in bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Some writers and erasers in bacteria are versatile in modifications of proteins with various acylations. For examples, CobB has been shown as a de-acetylase in E. coli and as a dehydroxybutyrylase in Proteus mirabilis 50 . Acetylation and succinylation are two representative PTMs in bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, 36 we used western blot to demonstrate that Khib is an evolutionarily-conserved PTM in 37 wheat and its donators, with the highest Khib abundance occurring in hexaploidy wheat. 38 Additionally, global profiling using affinity purification and mass spectroscopy of 2-39 hydroxyisobutyrylome revealed that there were 3348 lysine modification sites from 40 1074 proteins in common wheat (Triticum aestivum L.). Moreover, bioinformatic data 41 indicated that Khib proteins participate in a wide variety of biological and metabolic 42 pathways.…”
mentioning
confidence: 99%
“…Proteasomes of prokaryotes have been found only in Actinomycetes [ 95 ], where M. tuberculosis is one of the few bacteria known to have proteasomes on which relatively detailed research about mechanism and function has been performed. Its target proteins are involved in multiple aspects, such as substance metabolism in carbon metabolism and fatty acid metabolism, signaling pathways, toxic and antitoxic factors and cell wall and cell membrane components, and are related to the pathogenicity of Mtb [ 27 ]. Therefore, its proteasome is considered a new drug target for Mtb treatment.…”
Section: Pupylationmentioning
confidence: 99%
“…Mtb mainly inhabits host macrophages after infection. Studies have shown that pupylation and the proteasome are key elements that prevent the removal from host macrophages [ 27 , 98 ]. Furthermore, in the Mtb proteasome pathway, Pup serves as a protein modifier and provides an important means for identifying and characterizing Mtb substrates targeted to the proteasome.…”
Section: Pupylationmentioning
confidence: 99%